Transjugular Intrahepatic Portosystemic Shunt in Liver Transplant Recipients: Outcomes in Six Adult Patients. (May 2023) - Masek, Jan; Fejfar, Tomas; Frankova, Sona; Husova, Libuse; Krajina, Antonin; Renc, Ondrej; Chovanec, Vendelin; Raupach, Jan
Objectives: Transjugular intrahepatic portosystemic shunt (TIPS) is regularly used in treatment of clinically significant portal hypertension. Liver transplant recipients are, however, rarely indicated for the procedure. The study retrospectively examines the results of TIPS placement in 6 patients after OLT. Methods: 4 males and 2 females (aged 36 to 62 years), treated with TIPS between 2007 a 2018, were included in the study. 5 patients had previously undergone liver transplantation for liver graft cirrhosis, 1 patient for Budd-Chiari syndrome. The piggyback caval reconstruction technique was selected in 4/6 cases. PH developed after OLT due to the recurrence of underlying liver condition and sinusoidal obstruction syndrome in half of the cases, respectively. Indications for TIPS were refractory ascites in 4 cases and variceal bleeding in 2 cases. Results: Standard TIPS technique was used and technical success was achieved in all cases with a procedure-related complication in 1 patient. One patient died shortly after TIPS placement. The remaining patients all reported regression of clinically significant PH. Late complications appeared in 2 patients. Liver retransplantation after TIPS creation was performed in 1 case. Median TIPS patency was 55 months. 2/6 patient continue to thrive with a patent shunt. Conclusions: Transjugular intrahepatic portosystemic shunt in OLT recipients is technically feasible. Favorable clinical outcomes were reported particularly in patients treated for sinusoidal obstruction syndrome who were indicated to TIPS for refractory ascites.